2017
DOI: 10.1188/17.cjon.e260-e266
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Effective Standards of Care: Supporting the Administration of T-VEC for Patients With Advanced Melanoma in the Outpatient Oncology Setting

Abstract: T-VEC posed safety and logistical challenges that were successfully addressed and implemented. To date, 16 patients with locoregionally advanced melanoma have been treated with T-VEC. No adverse events occurred related to preparation or administration, which opens the door for similar therapies in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Simultaneously, when the tumour cells lysed, the viruses within them are also released to infect and kill other tumour cells [28,29] to form a cascade ampli cation effect. In recent years, with increasing study, many types of OVs have been approved for marketing, such as H101 [30] approved in China, T-VEC [31] approved in the USA, and the Japanese herpes simplex virus Deltyact [32] . These marketed oncolytic virus drugs provide a good prospect and important motivation for the development of OVs.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, when the tumour cells lysed, the viruses within them are also released to infect and kill other tumour cells [28,29] to form a cascade ampli cation effect. In recent years, with increasing study, many types of OVs have been approved for marketing, such as H101 [30] approved in China, T-VEC [31] approved in the USA, and the Japanese herpes simplex virus Deltyact [32] . These marketed oncolytic virus drugs provide a good prospect and important motivation for the development of OVs.…”
Section: Discussionmentioning
confidence: 99%
“…After the tumour cells are lysed, the viruses within them are also released to infect and kill other tumour cells 26,27 , which forms a cascade amplification effect. In recent years, several types of OVs have been approved, such as H101 28 in China, T-VEC 29 in the USA, and the Japanese www.nature.com/scientificreports/ herpes simplex virus Deltyact 30 . These marketed OV drugs bring a good prospect and important motivation for the development of OVs.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that most detectable virus from evaluated sites waned by 7 days postexposure. 14,22 TVEC is classified as a BSL2-level agent at MSK, in accordance with FDA guidance, and this dictates preparation and environmental management for TVEC. Agent preparation by trained pharmacy personnel occurs in a negative-pressure room biosafety cabinent (BSC) using a closed transfer system.…”
Section: Tvec: Summary and Recommendations For Infection Preventionmentioning
confidence: 99%
“…Additionally, a dedicated contact isolation precaution indicator is placed in the patient's electronic medical record, which serves to alert staff to recent treatment with TVEC and the need for contact precautions. 22 Entry and removal of the indicator is undertaken by the clinical support teams. Precautions are instituted until all lesions are healed or scabbed as determined by direct observation at follow-up or day 7 following injection of TVEC, whichever is longer.…”
Section: Tvec: Summary and Recommendations For Infection Preventionmentioning
confidence: 99%